O‘ZBEK VA INGLIZ TILLARIDA IDIOMALARNING LINGVISTIK TAHLILI - Baxieva, M.T. (SCIENCE and SOCIETY, 2025)
The article is presented a linguistic analysis of idioms in Uzbek and English. It explores key features of idioms such as stability, figurative meaning, imagery, and cultural specificity. Uzbek idioms are mainly rooted in folk thinking and agrarian lifestyle, while English idioms often reflect metaphorical and ironic aspects.